TANTANGAN DAN PELUANG IMPLEMENTASI SISTEM INFORMASI MANAJEMEN (SIM) DI LEMBAGA PENDIDIKAN ISLAM: Challenges and Opportunities in the Implementation of Management Information Systems in Islamic Educational Institutions - Ropik, Ikbal; Rosadi, Adi (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
This research explores the challenges and opportunities in implementing Management Information Systems (MIS) in Islamic Education Institutions.  Management Information Systems plays an important role in improving the efficiency and effectiveness of resource management, while strengthening the trust of various related parties. This study uses the literature review method by analyzing relevant literature, journals and case studies. The results show that the implementation of SIM can facilitate access to information, improve reporting regularity, and strengthen academic and administrative monitoring and evaluation. However, the implementation faces several obstacles, such as lack of understanding of technology, limited resources, resistance to change, and data security issues. To overcome these challenges, a holistic approach is needed through technology training, effective change management, and strengthening data security policies. In addition, increased understanding and support from policy makers are also key factors in successful SIM implementation. With the right strategy, SIM can be optimally utilized to improve the quality of education management in Islamic Education Institutions.